Detection of Polarization and Topological Charge Based on Multidimensional Field of Metasurface - Jing Luan; Sikang Yang; Deming Liu; Minming Zhang (IEEE Photonics Journal, 2020)
Integrating multiple functionalities into one single device is of great importance for ever-growing demand of photonic device. Optical vortex beam contains orbital angular momentum (OAM) and spin angular momentum (SAM) associated with phase and polarization singularities respectively, which has contributed to various application including optical manipulation, optical trapping and high-speed optical communication. Traditional methods to detect its phase and polarization mostly focus on the functionality of single dimensional optical field. However, quite different from the previous reports, we here propose a novel approach to measure the phase and polarization state based on the full use of near and far-field light functionalities in one single metadevice, which supports spin-controlled surface plasmon polaritons (SPPs) and topological charge-dependent focus spot position. On the one hand, this design makes the most of multidimensional field optical scattering characteristics to rich the functions of metadevice. On the other hand, it provides a novel concept to recognize various angular momentum information of vortex beam. We believe that such design will have great potential for the integration of different sub-wavelength optical components.